The Narrative Subject Storytelling in the Age of the Internet - Schachtner, Christina; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2020)
This open access book considers the stories of adolescents and young adults from different regions of the world who use digital media as instruments and stages for storytelling, or who make themselves the subject of storytelling. These narratives discuss interconnectedness, self-staging, and managing boundaries. From the perspective of media and cultural research, they can be read as responses to the challenges of contemporary society. Providing empirical evidence and thought-provoking explanations, this book will be useful to students and scholars who wish to uncover how ongoing processes of cultural transformation are reflected in the thoughts and feelings of the internet generation. .
1. Introduction -- 2. Storytelling as a Cultural Practice and Life Form -- 3. The Narrative Space of the Internet -- 4. The Net Generation$1 (Bs Stories: A Typology -- 5. A Theoretical Postscript: Time, Space, the Self and the You, and Digital Media as Narrative Constructions -- 6. Narrating as an Answer to Socio-Cultural Challenges -- 7. Narrative Production of Culture.s
Keywords: Communication; Social media; Digital media; Media and Communication; Social Media; Digital and New Media